Online Teaching of Rural Multi-Grade Classes in the Context of COVID-19: Proposing a Holistic Approach - Farokh Feizi; Morteza Bakhtiarvand (RIRAI Publisher, 2020)
This study addresses the educational challenges faced by students in rural multi-grade classes in the context of the global epidemic of Covid 19. Rural students in this course face unprecedented challenges in trying to adapt to a new way of life and learning. This study was conducted with the aim of creating a better future for these students and in line with critical research of the current situation. In order to collect data, participatory action research method was used. A total of 12 students from elementary multi-grade classes (fourth, fifth and sixth grades) and 6 teachers participated in this study. This study answers two key questions: What are the learning challenges for rural learners during Covid 19? How can their teaching and learning be enhanced? The results showed that while our education decision-making system promoted online learning as the only alternative at the time, many rural students were deprived of teaching and learning. This is due to reasons such as lack of hardware resources for Internet connection, lack of Internet network coverage in many villages, poor learning management system, economic poverty, heavy financial cost of Internet use, weakness or lack of necessary technological knowledge in some Rural teachers, the lack of Internet cafes in rural areas, the lack of fixed ADSL Internet in rural areas, has not been able to meet the educational needs of rural students.